Uncle Tom : from martyr to traitor - Spingarn, Adena, 1981- (Stanford University Press, 2018)
This book tells the story of how Uncle Tom, the Christ-like protagonist of Uncle Tom's Cabin, became a racial epithet and why Americans have been invoking this controversial figure for more than 160 years.